Ferroelectrics: Reversible Modification of Ferromagnetism through Electrically Controlled Morphology (Adv. Electron. Mater. 7/2019). (9th July 2019) - Vinai, Giovanni; Motti, Federico; Bonanni, Valentina; Petrov, Aleksander Yu.; Benedetti, Stefania; Rinaldi, Christian; Stella, Mattia; Cassese, Damiano; Prato, Stefano; Cantoni, Matteo; Rossi, Giorgio; Panaccione, Giancarlo; et al.
Abstract : In article number 1900150, Giovanni Vinai and co‐workers show that electrical switching in Fe x Mn1− x /PMN‐PT causes surface cracks 100‐nm deep to reversibly appear and disappear from the surface of a sample. Corresponding to these morphological changes, XMCD and micro‐MOKE measurements show that the magnetic response of Fe x Mn1− x is also locally modified.